Toolpath generation for asymmetric mandrel-free spinning. (2017) - Loukaides, Evripides G.; Russo, Iacopo M.
Abstract: Spinning of sheet metal traditionally employs a mandrel to form axisymmetric parts. In this work, forming of highly asymmetric parts through spinning is shown to be possible without the use of dedicated tooling through several physical trials. This technology eliminates the need for a mandrel and hence significantly reduces costs, lead times and material use. There is literature establishing the feasibility of spun asymmetric parts using dedicated tooling as well as work suggesting the potential for mandrel-free asymmetric parts, but this is the first time the latter is demonstrated in practice. This paper describes the methodology for designing blanks and toolpaths for this process and presents the results of the physical trials.